Air density dependence of the PTW 34013 ionization chamber for soft X-ray. (September 2016) - del Río, J. Torres; Forastero, C.; Tornero-López, A.M.; de la Vega, J.M.; Guirado, D.; Pérez-Calatayud, J.; Lallena, A.M.
Abstract : Introduction: It has been proved that some ionization chambers, when measuring low energy brachytherapy or soft X-ray sources, show a dependence with the air density that it is not entirely corrected with the usual pressure/temperature correction factor, k TP . This is due to the chamber dimensions and materials forming it. Purpose: To determine if the response of PTW 34013 chamber, used for dose measurements in superficial radiotherapy, is fully corrected with k TP or a residual air density dependence remains. Materials and methods: Measurements for 70 and 200 kVp X-ray beams, generated by a MAXISHOT.200 cabinet, have been performed using a pressurized chamber. Raw data have been corrected with k TP and normalized to its value in standard atmospheric conditions (760 mmHg and 20 °C). Results: The corrected measurements for both beams still show a linear dependence with the normalized density ρ / ρ 0, ρ 0 being the density in standard atmospheric conditions. When the air density is below ρ 0, k TP undercorrects the measurement, and the contrary occurs when ρ > ρ 0 . In our city, with 700 m AMSL, usual atmospheric conditions will cause 1.2% undercorrection for the 70 kV beam and 2.5% for the 200 kV beam. Conclusion: Despite its dimensions, the dependence of the PTW 34013 ionization chamber with the air density is not fully corrected with k TP . The weather or the altitude of the place where measurements are carried out will require an additional correction to reach the accuracy level required in radiotherapy. Disclosure: We thank to PTW for material support.